Development of Smart Hydroponic System using Internet of Things - Abdul Hayu, Anis; Homam, Mariyam Jamilah (Evolution in Electrical and Electronic Engineering, 2023)
The introduction of IoT technology into hydroponics has resulted in considerable changes in traditional farming methods. By seamlessly integrating IoT capabilities, farmers may rigorously monitor and adjust critical environmental variables. The goal of this work is to build an intelligent hydroponic system that uses IoT to fine-tune temperature, humidity, water levels, and pH levels, assuring an optimal environment for plant growth. Sensors strategically placed throughout the hydroponic setup are used to actively monitor and manage these factors. This system includes several key features, such as automatic control of water pumps to maintain adequate hydration levels, fan activation when the temperature reaches 34°C, as signalled by the Blynk app, and real-time pH level monitoring via the same app to maintain proper acidity levels. Automation and control features are also evaluated to certify the precise responsiveness of sensors, pumps, and other components in accordance with set requirements. This evaluation aids in determining the system's effectiveness as well as the general health of the farmed plants. Finally, the combination of IoT technology and hydroponics emerges as a viable technique for improving plant growth circumstances. The resulting smart hydroponic system is not only a practical solution, but also an effective alternative to modern agricultural methods.